Development of Problem Based Learning E-Module on Two Variable Linear Equation Systems (APPLICATION: Applied science in Learning Research, 2023)
The aim of this research is to figure out how to construct e-modules based on problem-based learning on two-variable linear equation system that from a valid, practical, and effective. This research employs to conduct a development study using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. The research analysis technique is using a validity test in the form of scores from material experts, media experts, and the value of teacher responses to e-modules using questionnaire scores. The goal of the practicality test to determine the study effectiveness is in the form of student responses using pretest and posttest scores. The results of this research resulted in an e-module product. To determine the product's feasibility using validation, practicality, and effectiveness tests. The resulting assessment by material experts got a score of 89% with a classification of valid or feasible. The resulting assessment by media experts got a score of 84% with a valid or feasible to use. The results of the educator's response questionnaire scored 86% with a classification of valid or feasible. The results of the student response questionnaire got a score of 81% with a very practical classification. The results of the pretest and posttest of students got a score of 56% with a classification of quite effective to use. Based on these results, the conclusion of the research is the development of an e-module based on problem-based learning on the material of a two-variable linear equation system that is valid, practical, and quite effective to use.